Assessing the Threshold of Need for Supplemental Damping in Seismic Base Isolation of Multistory Buildings - Ali Reza Babaeian Amini; Peyman Narjabadifam; Gholam Reza Ostadi Asl; Samad Emamverdi; Shahram Derogar; Bertug Ozarisoy (Shock and Vibration)
The comprehension of the threshold for the need of supplemental dampers in the base isolation of multistory buildings could be beneficial in the advancement of the application of base isolation to achieve seismic safety. In this study, stick models of 1-, 4-, 7-, 10-, 13-, 16-, and 19-story buildings were designed in fixed-base, simply base-isolated, and damping-assisted base-isolated scenarios. The isolation system considered is the well-known friction pendulum system, with supplemental damping provided by widely used viscous dampers. Time history analyses were conducted using seven far-fault accelerograms and seven near-fault accelerograms. Seismic performances were evaluated in terms of base shear values, story accelerations, interstory drifts, and story shears. The results indicate that base isolation is highly effective in controlling seismic responses in both far-fault and near-fault earthquakes, with average base shear values in the base-isolated models reduced by approximately 60%–75% compared with the fixed-base models. Displacements, accelerations, drifts, and story shears were also decreased by more than 50% compared with the fixed-base models. Base isolation demonstrated acceptable performance in the 4-, 7-, and 10-story models, but supplemental damping was necessary for effective structural control of the 13-story model in near-fault earthquakes, as well as the 16-story and 19-story models in both far-fault and near-fault earthquakes. The incorporation of supplemental damping significantly enhances structural control by further mitigating displacements, shears, and accelerations.